Is age just a number? The impact of age-diversity practices and workers' age on health and well-being - Sousa, I. C. (2018)
Workforces across the world are ageing. Research has been focusing on how Human Resources Management (HRM) can develop and promote sustainable careers for workers of all ages (e.g. Kooij et al., 2013; Schalk et al., 2010; Truxillo, Cadiz, & Hammer, 2015). This study tests two moderation hypotheses: age moderates the effect of perceived age-diversity practices (1) on perceived health and (2) on well-being. Human Resources (HR) practices that consider the needs, goals and preferences of workers of all ages – age-diversity practices – can be a strategy to ensure workers’ well-being and health. Perceived age-diversity practices refer to the degree to which individuals perceive that workers of all ages receive non-discriminatory treatment in terms of organisational practices, policies and procedures (Boehm, Kunze, & Bruch, 2014; Kunze, Boehm, & Bruch, 2013). Organisations can implement these practices to support workers’ health and well-being over time, by adjusting the physical work environment (e.g., ergonomic aspects) and fostering knowledge and skills. Age can have an important role in the impact of perceived age-diversity practices on health and well-being. The assumption is that these practices are especially important for older workers as they are more likely to experience health limitations due to the ageing process (Hansson, DeKoekkoek, Neece, & Patterson, 1997), and they are frequently the target of age discrimination in the workplace (e.g., Finkelstein, Burke, & Raju, 1995; Posthuma & Campion, 2009). A sample of 410 participants aged between 19 and 67 years old (M = 37.74, SD = 12.93) answered to a questionnaire with an on-line and a paper version. The moderation hypotheses were tested by Multiple Linear Regression using PROCESS macro for SPSS (Hayes, 2012). Findings supported the first hypothesis, suggesting that as increases age, also increases the effect of perceived age-diversity practices on perceived health, which means that as age increased, this relationship became more important. The second hypothesis was not supported, because the moderator effect of age was not significant. However, perceived age-diversity practices had a significant main effect on well-being, emphasising the importance of these practices to retain all workers, regardless of their age. These findings suggest that organisations should develop age-diversity practices to improve the well-being of workers of all ages, and that they could be particularly relevant for older workers’ health.